1977
DOI: 10.1073/pnas.74.10.4214
|View full text |Cite
|
Sign up to set email alerts
|

Release of ovoperoxidase from sea urchin eggs hardens the fertilization membrane with tyrosine crosslinks

Abstract: One feature of fertilization is the alteration of the vitelline layer, by components released from the e, to produce an elevated, covalently crosslinked, hard, insoluble, fertilization membrane. The following evidence indicates that crosslinking and hardening are caused by the production of diand trityrosyl residues, by oxidation of protein-bound tyrosyl residues in thepresence of a peroxidase. Hardening of the fertilization membrane, as evidenced by its loss of solubility in 50 mM dithiothreitol, is inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
168
0
3

Year Published

1983
1983
2008
2008

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(172 citation statements)
references
References 27 publications
1
168
0
3
Order By: Relevance
“…Cherr et al (1988) also show gold u In sea urchins, hardening of the fertilization enveloDe (analogous to the ZP) is catalyzed by a CG ovoper-oxidase and is associated with a slow block to polyspermy (Foerder and Shapiro, 1977;Hall, 1978). Mammalian CG (mouse) have also been shown cytochemically to contain an ovoperoxidase by staining them with 3,3'-diaminobenzidine (DAB) in the presence of H,02 .…”
Section: Proteinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cherr et al (1988) also show gold u In sea urchins, hardening of the fertilization enveloDe (analogous to the ZP) is catalyzed by a CG ovoper-oxidase and is associated with a slow block to polyspermy (Foerder and Shapiro, 1977;Hall, 1978). Mammalian CG (mouse) have also been shown cytochemically to contain an ovoperoxidase by staining them with 3,3'-diaminobenzidine (DAB) in the presence of H,02 .…”
Section: Proteinasesmentioning
confidence: 99%
“…Since ZP hardening is inhibited by the tyrosine analogues tyramine and N-acetyl-L-tyrosine (8 l% and 73%, respectively), the ovoperoxidase probably functions in hardening of the ZP by cross-linking tyrosine residues . The hardening of the fertilization envelope in echinoderm embryos establishes a slow block to polyspermy (Foerder and Shapiro, 1977;Hall, 1978), and ZP hardening could serve a similar function in mammals. It has also been suggested that ZP hardening in mammals protects the developing pre-implantation embryo (Cran, 1989).…”
Section: Ovoperoxidasementioning
confidence: 99%
“…We examined whether the oviductal factor responsible for ZP changes resistance to proteolysis and spermoocyte interaction matched any of the previously described factors, such as proteinases (24,25), a peroxidase (26), and a disulfide bond-forming reagent (27) that have been described as factors responsible for cortical granule effects. When pig IVM oocytes were incubated for 30 min in bOF with a mixture of proteinase inhibitors, the ZP did not dissolve even after 206 min in pronase solution, compared with 1 min in control oocytes.…”
Section: Oviduct-specific Glycoprotein Seems To Be Responsible For Thementioning
confidence: 99%
“…A possible role for the mauG gene product at the stage of cross-linking of the two methylamine-dehydrogenase Lchain tryptophan residues is suggested by the involvement of peroxidases in the formation of dityrosine cross-links between proteins in the sea urchin egg fertilisation envelope (Foerder and Shapiro, 1977;Hall, 1978), the embryo envelope of the brine shrimp Artemia salina (Roels, 1971) and the bristle cuticle of lepidopteran larvae (Locke, 1969). Furthermore, the reaction cycle of yeast cytochrome c peroxidase involves the one electron oxidation of an active site byptophan residue to a tryptophan radical (Sivaraja et al, 1989); this implies that the putative mauG gene product, functioning as a peroxidase, may be able to utilise H,O, to initiate a free-radical-mediated cross-linking of the two Lchain tryptophan residues forming the TTQ prosthetic group.…”
Section: Methylamine-dehydrogenase L-subunit Polypeptides Synthesisedmentioning
confidence: 99%